YouTube in Dictogloss Technique for English Language Teaching (ELT) class - Wati, Hera (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2021)
The use of YouTube in teaching the English language plays a leading role in helping learners understand their English lessons. It can improve the performance of students and upgrade their levels in English courses. In other words, YouTube presented a substantial influence on students’ understanding of English. Also, this paper found that YouTube could be a good material to incorporate English lessons and it can help with understanding the lesson as well. It should be considered by English teachers in the classroom since many of the learners’ responses in this study were positive. In short, the study showed that the YouTube website can be an effective method in dealing with students’ difficulties and barriers in understanding English. It is conceived to be more effective and successful than textbook-based English courses in promoting better learning of English.